SWEET11b transports both sugar and cytokinin in developing barley grains - Radchuk, Volodymyr; Belew, Zeinu M; Gündel, Andre; Mayer, Simon; Hilo, Alexander; Hensel, Goetz; Sharma, Rajiv; Neumann, Kerstin; Ortleb, Stefan; Wagner, Steffen; Muszynska, Aleksandra; Crocoll, Christoph; et al. (The Plant cell, 2023)
Even though Sugars Will Eventually be Exported Transporters (SWEETs) have been found in every sequenced plant genome, a comprehensive understanding of their functionality is lacking. In this study, we focused on the SWEET family of barley (Hordeum vulgare). A radiotracer assay revealed that expressing HvSWEET11b in African clawed frog (Xenopus laevis) oocytes facilitated the bidirectional transfer of not only just sucrose and glucose, but also cytokinin. Barley plants harboring a loss-of-function mutation of HvSWEET11b could not set viable grains, while the distribution of sucrose and cytokinin was altered in developing grains of plants in which the gene was knocked down. Sucrose allocation within transgenic grains was disrupted, which is consistent with the changes to the cytokinin gradient across grains, as visualized by magnetic resonance imaging and Fourier transform infrared spectroscopy microimaging. Decreasing HvSWEET11b expression in developing grains reduced overall grain size, sink strength, the number of endopolyploid endosperm cells, and the contents of starch and protein. The control exerted by HvSWEET11b over sugars and cytokinins likely predetermines their synergy, resulting in adjustments to the grain's biochemistry and transcriptome.
Keywords: Plant Proteins; Cytokinins; Sucrose; ječmen (rod); cukry; Hordeum; sacharosa; rostlinné proteiny; Sugars; cytokininy